1996
DOI: 10.1063/1.116382
|View full text |Cite
|
Sign up to set email alerts
|

Metal-insulator-semiconductor solar cells with silicon oxynitride tunnel insulator by using rapid thermal processing

Abstract: Metal-insulator-semiconductor (MIS) solar cells were prepared with silicon oxynitride as tunnel insulator by using rapid thermal processing (RTP). During the reaction of NH3 at the silicon surface the growing of the oxynitride layer was investigated at temperatures up to 950 °C and layer thicknesses up to 2 nm. The elemental composition of the layer was characterized by using Auger electron spectroscopy (AES). Extensive electrical characterizations on MIS tunnel diodes and MIS cells were carried out and an imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
4

Year Published

1997
1997
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 0 publications
0
4
0
4
Order By: Relevance
“…2 In plasma-deposited silicon nitride films, this hydrogen originates from the precursor gases used in the deposition process, and it may be bonded to nitrogen and silicon or trapped in molecular or atomic form in microvoids within the network structure. 3,4,5 Silicon nitride is used in inversion layer solar cells, 6 thin film transistors, 7 and memory devices 8 because of its excellent dielectric properties. Particularly useful is its high dielectric permittiviy, which makes it a promising candidate to substitute silicon dioxide in the gate structure of field effect transistors.…”
Section: Introductionmentioning
confidence: 99%
“…2 In plasma-deposited silicon nitride films, this hydrogen originates from the precursor gases used in the deposition process, and it may be bonded to nitrogen and silicon or trapped in molecular or atomic form in microvoids within the network structure. 3,4,5 Silicon nitride is used in inversion layer solar cells, 6 thin film transistors, 7 and memory devices 8 because of its excellent dielectric properties. Particularly useful is its high dielectric permittiviy, which makes it a promising candidate to substitute silicon dioxide in the gate structure of field effect transistors.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogenated amorphous silicon nitride (a-SiN x :H) is a widely used material with many technological applications [1,2] . In recent years studies have been shown that, by changing the growth conditions, especially after the thermal annealing process [3,4] , silicon nano-dots are clearly observed in the Si-rich SiN x :H thin films deposited by plasma assisted processes.…”
Section: Introductionmentioning
confidence: 99%
“…No entanto, no caso LPD, o tempo de preparação é longo e não existe um controle exato da espessura (CHEN, 2002;YEH, 1994;1995 (TOQUETTI, 2005;SANTOS, 1995(c); NULMAN, 1986;MOSLEHI, 1989;CHIOU, 1990;2004(b); GAVARTI, 2005). (LU, 1995;BEYER, 1996;YAO, 1994;CHANG, 2004(b) Deve-se tomar um cuidado rigoroso com a proporção molar da mistura de H2/O2, pois caso esta seja maior do que 2, a mistura torna-se explosiva ao ser injetada em um forno aquecido (SOUZA, 2006).…”
Section: 05unclassified